Determinants of University Program Choices among Students: A Case Study of Universities in Garowe, Puntland-Somalia - Ahmed, Mohamed (African Journal of Education and Practice, 2025)
Purpose: This study examines the determinants of university program choices among students in Garowe, Puntland-Somalia, using a mixed-methods approach. The objective is to analyze how students' choices are influenced by institutional characteristics, family dynamics, socioeconomic backgrounds, and peer groups. Methodology: A descriptive survey design was employed, incorporating quantitative data from structured questionnaires and qualitative insights from focus group discussions (FGDs) and key informant interviews (KIIs). Findings: The study found that students’ perception of institutions and program offerings was not a significant factor in their decision-making. A majority of respondents (71%) disagreed or strongly disagreed that the reputation of their institution influenced their choice, while 72% did not consider program offerings as a determining factor. Family factors played a crucial role, with 66% of respondents reporting that parental education influenced their choice, 69% acknowledging the impact of family expectations, and 81% agreeing that financial support from parents affected their decision. Additionally, financial factors were significant, as 73% believed that program costs impacted their choice, 76% recognized the influence of their financial circumstances, and 70% stated that their financial situation directly shaped their decision. Unique Contribution to Theory, Practice and Policy: The study highlights the need for diverse educational opportunities to accommodate students' interests and financial situations. It also recommends enhanced career guidance services to assist students in making informed decisions. Furthermore, the study suggests implementing financial support mechanisms to reduce economic barriers and ensure equitable access to higher education.